E-Government Performance in Developing Countries: A Comparative Study Across Cities - Wijaya, Aditya Pranata (Asian Digital Governance Problems, 2026)
Purpose: E government has become a key instrument for public sector reform, particularly in developing countries where urban governments face increasing demands for efficient, transparent, and accessible public services. While national level assessments provide useful benchmarks, they often overlook variations in e government performance at the city level, where implementation directly affects citizens. Subjects and Methods: This study employs a comparative cross sectional design to examine e government performance across selected cities in developing countries. Using secondary data from official municipal websites, policy documents, and international reports, the study assesses multiple dimensions of e government performance, including online service availability, usability, information quality, transparency, and citizen engagement. A standardized set of indicators is applied to enable systematic comparison across cities. Results: The findings reveal considerable variation in e government performance among the cities studied. Overall, cities demonstrate stronger performance in basic service provision and information dissemination than in transparency and citizen engagement. While some cities show relatively balanced implementation across dimensions, others exhibit fragmented or uneven performance, indicating differences in institutional capacity and governance orientation. Conclusions: The study concludes that e government performance in developing cities remains largely service oriented and has yet to fully realize its potential as a tool for participatory and transparent governance. Effective e government requires not only technological adoption but also stronger institutional commitment to openness, accountability, and citizen involvement. These findings underscore the importance of aligning digital initiatives with broader governance reforms at the local level.